2014
DOI: 10.1016/j.fertnstert.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of semen analysis as a test of male fertility and anticipated needs from newer tests

Abstract: Semen analysis is the first step to identify male factor infertility. Standardized methods of semen analysis are available allowing accurate assessment of sperm quality and comparison amongst laboratories. Population based references ranges are available for standard semen and sperm parameters. Sperm numbers and morphology are associated with time to natural pregnancy whereas sperm motility may be less predictive. Routine semen analysis does not measure the fertilizing potential of spermatozoa and the complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
164
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(173 citation statements)
references
References 57 publications
7
164
0
2
Order By: Relevance
“…Although a semen analysis is the best predictive test we have to date, it clearly falls short of a true diagnosis (5,6). Indeed, several studies have shown that men with sperm numbers (7)(8)(9), morphology (8,10), and motility (11)(12)(13)(14)(15)(16)(17) below the thresholds outlined by the WHO can be fertile. Furthermore, there are many instances of men with normal sperm parameters that are infertile (13, 18 -20).…”
mentioning
confidence: 99%
“…Although a semen analysis is the best predictive test we have to date, it clearly falls short of a true diagnosis (5,6). Indeed, several studies have shown that men with sperm numbers (7)(8)(9), morphology (8,10), and motility (11)(12)(13)(14)(15)(16)(17) below the thresholds outlined by the WHO can be fertile. Furthermore, there are many instances of men with normal sperm parameters that are infertile (13, 18 -20).…”
mentioning
confidence: 99%
“…Routine semen analysis is not a reliable method to determine the fertilising potential of spermatozoa and do not include the prediction of the changes that occur in the female reproductive tract before fertilisation. Thus, clinicians and researchers discuss that newer tests to predict the success of fertilisation are needed (Franken & Oehninger 2012, Wang & Swerdloff 2014). Indeed, current tests do not study spermatozoa ability to reach and fertilise the oocyte.…”
Section: Discussionmentioning
confidence: 99%
“…While the analyses conducted herein have been used to search for associations in chronic diseases and biomarkers such as serum lipids (Patel et al ., 2012), we are not aware of any published work focusing on human fecundity or related impairments such as conception delay or pregnancy loss. To this end, we cannot interpret our findings in the context of earlier work, but data‐driven techniques can be extended to include emerging biomarkers of male fecundity, such as sperm function tests or in vitro capacitation tests (Wang & Swerdloff, 2014). …”
Section: Discussionmentioning
confidence: 90%